Kelalaian Pelaku Usaha Terhadap Produk Tanpa Label Halal dan Informasi Kedaluarsa: Analisis Hukum Ekonomi Syariah dan Undang-Undang Perlindungan Konsumen - Abdussalam, Fahmi; Inayati, Anindya Aryu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The negligence of business actors who do not include halal labels, ingredient composition, and expiration dates on their products causes risks to consumers. Whereas product safety is very necessary to protect consumer rights. The purpose of this study is to analyze business actors who do not include halal labels, composition, and expiration dates from the perspective of Islamic economic law and consumer protection laws. The research method uses empirical juridical with a qualitative, legislative, and conceptual approach. This study was conducted on tempeh chip business actors in Tegal Regency. Data collection techniques used observation, interviews, and documentation. The analysis technique used an interactive model. The results of the study show that, according to Islamic economic law, business actors who do not include halal labels, product composition, and expiration dates are prohibited because they cause harm to the community, in this case, consumers. Meanwhile, according to the Consumer Protection Law, business actors are required to fulfill consumer rights in providing correct, clear, and honest information regarding the condition and guarantee of goods and/or services, so as not to endanger consumers. The findings of this study contribute to efforts to improve the enforcement of consumer protection laws.